2019
DOI: 10.1080/17482631.2019.1647401
|View full text |Cite
|
Sign up to set email alerts
|

Breathing through a troubled life – a phenomenological-hermeneutic study of chronic obstructive pulmonary disease patients’ lived experiences during the course of pulmonary rehabilitation

Abstract: Purpose: Exploring real-life experiences of Chronic Obstructive Pulmonary Disease (COPD) patients during rehabilitation can contribute with new knowledge of what has significance for their participation and chance for improved health and well-being. Therefore, this study aims to gain in-depth knowledge of COPD patients' lived experiences while following standard pulmonary out-patient rehabilitation. Methods: Combined participant observations and interviews were conducted among 21 participants in pulmonary reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Here we especially focused on what was essential to COPD patients in rehabilitation. In addition, previous findings from a preliminary study of COPD patients’ experiences of their participation in standard pulmonary rehabilitation [27,28] were considered along with practical issues.…”
Section: >C☺pd-life>> (Copd: Chronic Obstructive Pulmonary Disease)mentioning
confidence: 99%
See 2 more Smart Citations
“…Here we especially focused on what was essential to COPD patients in rehabilitation. In addition, previous findings from a preliminary study of COPD patients’ experiences of their participation in standard pulmonary rehabilitation [27,28] were considered along with practical issues.…”
Section: >C☺pd-life>> (Copd: Chronic Obstructive Pulmonary Disease)mentioning
confidence: 99%
“…This mainly concerned consultation according to their goals including adjustment in techniques and workload during exercising, injury treatment, instructions and guidance in performing daily activities in a more energy-conserving matter. Predefined educational topics were: breathing techniques, e.g., instruction in the use of the positive expiratory pressure (PEP) device, physical activity and training principles, lung anatomy and COPD, incontinence and pelvic exercise, maintaining physical activity and pain management [2,28]. During these educational sessions, the techniques were trained with intensive guidance from the physiotherapist.…”
Section: >C☺pd-life>> (Copd: Chronic Obstructive Pulmonary Disease)mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the present study suggest that constant dialogue with a telenurse may help individuals who are chronically ill to develop a broader perspective and resilience through their illness trajectory. Simonÿ et al (2019) reported that the considerable difficulty patients face when living with COPD hinder their prospects of overcoming the perceived lack of trust in their body during standard pulmonary rehabilitation. Providing breath management and physical recovery interventions on time is essential to allow people living with COPD to achieve vitality.…”
Section: Promising Role Of Telenursing In Light Of the Covid-19 Pandemicmentioning
confidence: 99%
“…In the last section of this paper I would like to develop the idea of recognition of the presence of anxiety in the so-called "affective niche", or affective scaffolding, which is a form of self-styled environment constructed in everyday life by the particular shaping of the affective tonality of our routines (by colors, music, lightning) 3 [4]. For this reason I would like to briefly consider two cases of implementing the phenomenological hermeneutics as sufficient approach in the research of anxiety protocols (see Simonÿ et al' research of nursing protocols and interviews on the patients' lived experience, and Alberto de Castro's implementation of hermeneutic technique) [7][8][9][10].…”
Section: Rm Rilkementioning
confidence: 99%